Pelatihan Pembuatan Materi Pembelajaran Menggunakan Canva - Andrian Syahputra; Rizki Maulida; Josep Febrian; Kevin Adrian (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Training in creating learning materials using Canva is becoming increasingly relevant in the context of modern education which is increasingly adopting technology. Canva, as an online graphic design platform, offers various features that enable teachers to create interesting, interactive and informative learning materials. However, this training also faces several challenges, including variations in technology skill levels among teachers and limited access and time. This research investigates the training process for creating learning materials using Canva and its impact on graphic design skills, use of technology, and student engagement in learning. The research results show that this training is effective in improving teachers' graphic design skills, expanding the use of technology in teaching, and increasing student engagement in the learning process. Practical implications of this research include the need for additional support and resources for teachers, as well as training approaches tailored to teachers' needs and skill levels. Further research could explore more effective strategies for overcoming these training-related challenges, as well as their long-term impact on the quality of learning.